The Effect of E-Booklet: CETING on Maternal Knowledge and Attitude Regarding Stunting at Integrated Health Posts for Toddlers in Gunung Wetan Village, Banyumas Regency - Hakim Ardhi Nugroho; Atika Dhiah Anggraeni (UM Purwokerto Press, 2024)
Background: The problem of short children (stunting) is one of the nutritional problems that is the focus of the Indonesian Government. Stunting is a condition of malnutrition that is related to nutritional deficiencies. Various efforts have been made to prevent stunting, one of which is health education using e-booklets. This research focuses on mothers' knowledge and attitudes regarding stunting prevention, because if health education is not provided, the stunting rate in Indonesia could increase. Method: This research is a quasi-experimental research with a pre-post-test without control group design. The research was conducted on 53 mothers who have toddlers aged under 2 years. The sampling technique used purposive sampling, the dependent variable was knowledge and attitude for the independent variable, the influence of ebooklets. Researchers used percentage and paired t-test analysis. Results: : The majority of respondents were aged 21-26 years, all of whom were female. At the education level, most of the respondents had elementary and junior high school education. The majority of the work of IRT respondents is 28 respondents. The average value of knowledge and attitudes after the intervention was good 29 has increased. while the average mother's attitude after the intervention was Good 25 increased. The p-value of the Paired T-test for knowledge is 0.001 and for attitude is 0.000. Conclusion: Ceting e-booklet media (preventing stunting) has an effect on efforts to increase mothers' knowledge and attitudes about stunting (0.000).